REPRESENTASI DISKRIMINASI TERHADAP PENYANDANG AUTISME SEBAGAI SAKSI DI PENGADILAN DALAM FILM INNOCENT WITNESS (Analisis Semiotika Charles Sanders Peirce) - Silalahi, Sisilia; Tsuroyya, (The Commercium, 2024)
Film is a social phenomenon that has many meanings. One phenomenon that is often raised in films is discrimination and stigmatisation that is also experienced by people with autism. One of the films that tells the phenomenon is Innocent Witness, which tells the story of a person with autism who becomes the sole witness in a murder case. To examine the film Innocent Witness, a descriptive qualitative approach is used using Charles Sanders Peirce's semiotic theory. This theory will be used to find out how the representation of discrimination against people with autism as witnesses in court in the film Innocent Witness. The data used in this research are 2 sequences in the film Innocent Witness in which there are 10 scenes depicting discrimination against people with autism. The results obtained from this research are that people with autism experience environmental discrimination that is not friendly to people with autism. Where people with autism have difficulty being in public places because it is very disturbing to their hearing. People with autism are also discriminated against because they are women with disabilities where patriarchy is still evident in South Korea. The discrimination against people with autism was also done so that the defendant would not be convicted and the reputation of the defence law firm would improve. Later, however, the discrimination against autistic people began to diminish as the truth of the case was finally revealed and the defendant confessed to his actions. Keywords: representation, discrimination, semiotics, autistic people, film, charles sanders peirce semiotic